PERANAN HUKUM DITENGAH DIGITALISASI INDUSTRI KEUANGAN - Dika Anggara Putra; Arina Novitasari; Avira Budianita (JURNAL KEADILAN HUKUM, 2024)
AbstractThe digitalization of the financial industri plays a very important role in the development of the progress of the financial system and the world economy, it is undeniable that all financial industries have entered the transition process from the conventional financial industri to a digital-based financial industri. This is evidenced by a report compiled by Bank Indonesia in the third quarter of 2023, electronic money with a transaction value increased by 10.34% (YoY) to reach IDR 116.54 trillion and digital banking transactions worth IDR 15,148 trillion with a growth rate of 12.8% (YoY). The government and related regulators must follow the development of legal products that serve as a legal umbrella in the process of developing the digitalization of the financial industri.Keywords: Digitalization, Legal Product Financial, Financial Industri